Effect of Porosity of Calcium Sulfate Beads on Ceftazidime Elution and in vitro Osteogenic Properties - Thitiyanaporn, Chaiyakorn; Thengchaisri, Naris; Udomkusonsri, Pareeya (Agriculture and Natural Resources, 2012)
The porosity of a drug delivery material is an important factor for enhancing drug release. A salt leaching technique was employed to create calcium sulfate (CS) beads with different pore sizes. CS was mixed with sodium chloride in ratios of 1:0 (control), 4:1, 2:1 and 1:1 weight per weight. Physical characteristics (weight, porosity level, compressive strength, microstructure and amount of ceftazidime released from CS) were compared among the different mixes. The percentage of total porosity increased depending on the amount of salt. The average amounts of ceftazidime (milligrams per gram of CS) were 59.10 ± 9.48, 79.00 ± 16.39, 89.39 ± 24.60 and 160.63 ± 46.84 and the duration of drug release was 6, 5, 5 and 4 d from the control, 4:1, 2:1 and 1:1 groups, respectively. The ratio of the total amount of ceftazidime release per weight of CS beads was positively correlated to the total porosity of the CS beads (R = 0.8152). The osteogenic effects of CS beads were compared between the control and the 1:1 group using human osteoblasts (h-OBs). There was a signiﬁ cant increase in the number of h-OBs that survived in 1:1 CS beads compared to the control on the ﬁ rst and seventh day after co-cultivation. In conclusion, the enhanced porosity of the CS beads by the salt leaching technique not only increased the drug release but also provided macroporous scaffolds stimulating osteoblast proliferation.